Fabrication of inverted ZnCuInS/ZnS based quantum-dot light-emitting diodes with the non-stoichiometric ZnO layers. (27th July 2021) - Biswas, Mohammad Mostafizur Rahman; Hossain, Md. Faruk; Okada, Hiroyuki
Abstract: The performance of the Cd-free quantum-dot light-emitting diode was investigated using un-doped and non-stoichiometric sputtered ZnO. Highly conductive metallic ZnO was sputtered with the presence of pure argon (Ar) gas, where the thickness was varied to enhance the structural, morphological, and electrical properties. The electrical properties of the fabricated ZnO were measured using the Hall measurement technique. Consequently, the device performance was validated by the mobility and carrier concentration of the sputtered ZnO film. In addition, from the X-ray diffraction analysis, it was confirmed that the ZnO film was grown on c (002)-axis orientation, parallel to the substrate surface. The morphological properties were also observed using a field-emission-scanning electron microscope to integrate with the crystalline growth conditions of XRD analysis. The external quantum efficiency of 1.02% and current efficiency of 1.86 cd A −1 were achieved with the mobility of 15.1 cm 2 V −1 s −1 and carrier concentration of 2.94 × 10 20 cm −3 of the ZnO film.